2010
DOI: 10.4049/jimmunol.1001513
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 as an Anti-Inflammatory Target and Modifier Gene in Cystic Fibrosis

Abstract: New treatments are needed to improve the health of people with cystic fibrosis (CF). Reducing lung-damaging inflammation is likely to be beneficial, but specific anti-inflammatory targets have not been identified. By combining cellular immunology with a population-based genetic modifier study, we examined TLR5 as an anti-inflammatory target and modifier gene in CF. Using two pairs of human CF and control airway epithelial cells, we demonstrated that the TLR5–flagellin interaction is a major mediator of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 69 publications
6
46
0
Order By: Relevance
“…It is therefore tempting to postulate that the hypofunctional TLR5 variant broadly impairs the inflammatory response to flagellated infection, resulting in reduced sepsisinduced organ failure and death. This idea is consistent with other studies showing that carriage of the variant is protective in inflammatory conditions, including systemic lupus erythematosus, cystic fibrosis (the variant is associated with a higher body mass index), and Crohn's disease (29)(30)(31). However, IL-10 is the sole cytokine that is consistently reduced in carriers of TLR5 1174T from Whole blood was stimulated with media, E. coli 0111:B4 LPS 10 ng/ml, S. typhimurium flagellin 500 ng/ml, heat-killed B. pseudomallei 1026b 2.5 3 10 6 CFU/ml, or heat-killed B. pseudomallei K96243 2.5 3 10 6 CFU/ml (K9) for 6 h. Inflammatory mediators were measured in plasma by multiplex bead assay or ELISA (IL-1b for B. pseudomallei only), normalized to monocyte count, and log 10 transformed for statistical analysis by linear regression.…”
Section: Discussionsupporting
confidence: 81%
“…It is therefore tempting to postulate that the hypofunctional TLR5 variant broadly impairs the inflammatory response to flagellated infection, resulting in reduced sepsisinduced organ failure and death. This idea is consistent with other studies showing that carriage of the variant is protective in inflammatory conditions, including systemic lupus erythematosus, cystic fibrosis (the variant is associated with a higher body mass index), and Crohn's disease (29)(30)(31). However, IL-10 is the sole cytokine that is consistently reduced in carriers of TLR5 1174T from Whole blood was stimulated with media, E. coli 0111:B4 LPS 10 ng/ml, S. typhimurium flagellin 500 ng/ml, heat-killed B. pseudomallei 1026b 2.5 3 10 6 CFU/ml, or heat-killed B. pseudomallei K96243 2.5 3 10 6 CFU/ml (K9) for 6 h. Inflammatory mediators were measured in plasma by multiplex bead assay or ELISA (IL-1b for B. pseudomallei only), normalized to monocyte count, and log 10 transformed for statistical analysis by linear regression.…”
Section: Discussionsupporting
confidence: 81%
“…3A). To dissect which mechanism(s) induce(s) MDSCs in chronic P. aeruginosa infection, we focused on flagellin because 1) infection with flagellated P. aeruginosa was associated with MDSC induction in our CF patient cohort, whereas nonflagellated microbes did not show any association with MDSCs in vivo; and 2) previous studies showed that among different PAMPs, flagellin recognition through TLR5 in particular plays a key role in leukocyte-P. aeruginosa interactions in CF lung disease (4,5,17,18). Our studies demonstrated that flagellin efficiently and dose-dependently induced MDSCs with a more potent capacity than GM-CSF did (Fig.…”
Section: Flagellated Pseudomonas Aeruginosa and Purified Flagellin Inmentioning
confidence: 99%
“…P. aeruginosa potently activates the innate arm of the immune system, an effect mainly mediated through pathogenassociated molecular patterns (PAMPs) and pattern recognition receptors. Among those, the TLR 5 ligand flagellin was found to play a key role in the recognition of P. aeruginosa (1)(2)(3)(4)(5). However, patients with chronic lung diseases, prototypically cystic fibrosis (CF) patients (6), are unable to eradicate the bacterium efficiently.…”
mentioning
confidence: 99%
“…These cytokines cause postischemic inflammation in the brain, subsequently leading to exacerbated primary brain damage (3,4). Previous work has demonstrated that activation of TLRs either by microbial or endogenous ligands results in an inflammatory response by delivering a signal from the intracellular TIR (Toll/IL-1 receptor) domain of TLR through a series of intracellular adaptor molecules, including MyD88, interleukin-1 receptorassociated kinase (IRAK) and TNF receptor associated factor 6 (TRAF6) (5,6). For example, IRAK and TRAF6 are recruited to the TLR complex via interaction with MyD88 (7) and activate nuclear factorkappa B (NF-κB), a transcription factor that regulates the expression of a wide array of genes involved in inflammatory responses, as well as the mitogenactivated protein kinases (MAPKs), such as extracellular signal-regulated kinase (ERK), p38 and c-jun N-terminal kinase (JNK) (8,9).…”
Section: Introductionmentioning
confidence: 99%